2022
DOI: 10.3390/foods11081089
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Determination of Mixed Pesticide Residues on Apple Surfaces by Surface-Enhanced Raman Spectroscopy

Abstract: Chlorpyrifos (CPF) and 2,4-dichlorophenoxyacetic acid (2,4-D) are insecticides and herbicides which has been widely used on farms. However, CPF and 2,4-D residues on corps can bring high risks to human health. Accurate detection of pesticide residues is important for controlling health risks caused by CPF and 2,4-D. Therefore, we developed a fast, sensitive, economical, and lossless surface-enhanced Raman spectroscopy (SERS)-based method for pesticide detection. It can rapidly and simultaneously determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…It might be caused by surface defects on the AgNPs-PDMS substrate, which give rise to uneven enhancement of the Raman signal. Nonetheless, the coefficients of determination achieved in this study are at the same level with previously reported SERS-based methods [ 41 , 42 , 56 ]. Considering that the priority of this study is to establish a method for the rapid screening of pesticide residues, the linearity of the regression equations should be acceptable for semi-quantitative SERS analysis.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…It might be caused by surface defects on the AgNPs-PDMS substrate, which give rise to uneven enhancement of the Raman signal. Nonetheless, the coefficients of determination achieved in this study are at the same level with previously reported SERS-based methods [ 41 , 42 , 56 ]. Considering that the priority of this study is to establish a method for the rapid screening of pesticide residues, the linearity of the regression equations should be acceptable for semi-quantitative SERS analysis.…”
Section: Resultssupporting
confidence: 87%
“…In another study, a flexible Au nanostars/polydimethylsiloxane (PDMS) substrate was recently developed for in-situ determination of methyl parathion on fruit [ 41 ]. Wang et al also reported the rapid detection of mixed chlorpyrifos and 2,4-dichlorophenoxyacetic acid residues on apple surfaces by using Ag colloid as a SERS substrate [ 42 ]. All these studies show the outstanding performance and great potential of applying a flexible substrate for fast and on-site SERS detection of pesticides on fruit surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In literature SERS technique has been used for detection of CPF in apple residues and their recovery rate is reported to be 87.97-97.06 %. [10] Thus PBI-SAH assemblies exhibit comparable detection potential using much easier fluorescence technique. We also used assemblies of PBI-SAH for detection of CPF in blood serum.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate the potential of PBI‐SAH assemblies for efficient detection of residues of CPF in apple. In literature SERS technique has been used for detection of CPF in apple residues and their recovery rate is reported to be 87.97–97.06 % [10] . Thus PBI‐SAH assemblies exhibit comparable detection potential using much easier fluorescence technique.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation